HAZOP Analysis and Research of Temporary Acid Adding System for High-Discharge Waste Liquid. (23rd February 2021) - Guo, Zan; Zou, Shuliang; Ma, Wenge; Dai, Haiyin
Abstract : To prevent the formation of salt from fission products of high-level radioactive liquid wastes (HLWs), a certain amount of acid is added to maintain the acidity of liquid waste. This study analyzes the accidents associated with the addition of acids in a factory by using the hazard and operability analysis (HAZOP), while elucidating the corresponding defects and risks of this approach. By improving the design of the system, the possibility of an accident is significantly reduced. This study can provide guidance for adding acids to treat other high-level waste liquids.